PENGELOLAAN LIMBAH KOTORAN AYAM MENJADI PUPUK ORGANIK PADAT OLEH KKN PMD UNIVERSITAS MATARAM DESA TUMBUH MULIA PERIODE 8 JULI s/d 21 AGUSTUS - Naya, Alifia; Juandra, Muhamad; Jurnal Wicara; Aprilia, Ochie; Mahdan, Saujana; Fibrianti, Riskia; Fitriah; Sa’ adatallayyali; Safitri, Yohana; Ramdani, Novrizal; Rahmawati, Kavia (Jurnal Wicara, 2025)
The Community Service Program (KKN) in Tumbuh Mulia Village identified a major agricultural problem: low crop productivity due to a lack of environmentally friendly and affordable fertilizers. The village's abundant chicken manure has not been optimally utilized, potentially polluting the environment. The project aimed to process chicken manure into organic fertilizer for local farmers. The manufacturing process involved mixing chicken manure, rice husks, dolomite, molasses, and AM11 microbial activator as a decomposer, followed by fermentation for approximately one week without turning. The fermentation results showed significant physical changes, including a crumblier texture, a blackish-brown color, and a reduced odor, making it suitable for agricultural use. This solid organic fertilizer product was then tested on residents' chili plants, which showed improved growth compared to before. This project not only provided a solution to the problem of livestock waste but also increased the community's knowledge and skills in processing waste into environmentally friendly products. Thus, this program contributes to strengthening sustainable agriculture while strengthening the synergy between universities and the community.